1992
DOI: 10.1007/bf02576298
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations ofd-lactate and its related metabolic intermediates in liver, blood, and muscle of diabetic and starved rats

Abstract: This is a report investigating the methylglyoxal (MG) bypass in animals, by which D-lactate is produced from triosephosphate via MG. Rats were made diabetic using streptozotocin or starved for 72 h. D-Lactate and various metabolites related to it, such as L-lactate, pyruvate, methylglyoxal, glucose, and inorganic phosphate, were measured in the blood plasma, liver, and skeletal muscle of the rats. Diabetic and starved rats had significantly higher levels of D-lactate in plasma, liver, and skeletal muscle compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
3
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 17 publications
1
29
3
2
Order By: Relevance
“…The D-lactate concentration of rat serum before fasting was 87.6 Ϯ 26.5, in fasting for 24 h was 35.1 Ϯ 5.2, and in fasting for 48 h was 25.5 Ϯ 7.2 M, while the body weight was 228 Ϯ 9.8, 186 Ϯ 5.8, and 183 Ϯ 6.8, respectively (mean Ϯ SD, n ϭ 5). Differing from the previous report by Kondoh et al (27) in which plasma D-lactate concentrations in fasted rats determined by the enzymatic (LDH) method were about two times higher than those in control rats, we observed the significant decrease of D-lactate concentrations in fasting (less than the half value of control). Although this discrepancy is not clearly explained, it might depend on the difference of the methodology for D-lactate determination.…”
Section: D-lactate Concentration In Fasted Rat Serumcontrasting
confidence: 85%
See 1 more Smart Citation
“…The D-lactate concentration of rat serum before fasting was 87.6 Ϯ 26.5, in fasting for 24 h was 35.1 Ϯ 5.2, and in fasting for 48 h was 25.5 Ϯ 7.2 M, while the body weight was 228 Ϯ 9.8, 186 Ϯ 5.8, and 183 Ϯ 6.8, respectively (mean Ϯ SD, n ϭ 5). Differing from the previous report by Kondoh et al (27) in which plasma D-lactate concentrations in fasted rats determined by the enzymatic (LDH) method were about two times higher than those in control rats, we observed the significant decrease of D-lactate concentrations in fasting (less than the half value of control). Although this discrepancy is not clearly explained, it might depend on the difference of the methodology for D-lactate determination.…”
Section: D-lactate Concentration In Fasted Rat Serumcontrasting
confidence: 85%
“…Using the present method, we examined the influence of fasting on the D-lactate concentration in rat serum, which was reported to increase (27). The representative chromatograms of serum sample were shown in Fig.…”
Section: D-lactate Concentration In Fasted Rat Serummentioning
confidence: 99%
“…The endogenous D-lactic acid is produced from methyglyoxal mediated by glyoxalase I and II in the metabolic pathway of glucose [1,2]. It has been reported that D-lactic acid concentration was significantly increased in the serum of diabetic animals [3,4] and patients [5]. This has been considered due to the accelerated production of its precursor, methyglyoxal, which causes the patient to develop diabetic complications under the diabetic stage [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 96%
“…The D-lactic acid concentration has been reported to increase in plasma of experimental animals such as diabetic rats and cats (Christopher et al, 1995;Kondoh et al, 1992Kondoh et al, , 1994, due to the enhanced production of its precurser, methylglyoxal, in diabetes. The increase of D-lactic acid concentration has also been reported in plasma of patients with diabetes mellitus (McLellan et al, 1992(McLellan et al, , 1994Beisswenger et al, 1999), suggesting that D-lactic acid might be one of the possible clinical markers for diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%